Diagnostic fi beroptic bronchoscopy in potential lung donors - M. Sh. Khubutiya; A. M. Gasanov; E. A. Tarabrin; E. I. Pervakova; T. E. Kallagov; D. F. Ibragimova (Трансплантология (Москва), 2016)
The article has summarized the global practice of the lung graft assessment with defining the absolute and relative criteria of donor lung suitability. The authors have presented their own experience of fiberoptic bronchoscopy 115 potential donors in the period from 2010 to 2015. The results of endoscopic examination of donor lungs were reviewed to determine the degree of the bronchial mucosa inflammation. A therapeutic fiberoptic bronchoscopy allowed clearing the bronchial lumen from pathologic contents and adequate preparing the lung graft in 29.6% of cases.